Training in the speciality of General and Family Medicine in Angola: A cross-sectional study - Clara T.L. da Silva Fernandes; Isabel N. da Mata Ferreira; Manuel F.D. dos Santos; Paulo Santos (African Journal of Primary Health Care & Family Medicine)
Background: Primary healthcare plays a crucial role in health system, acting as the first line of assistance in preventing, treating and caring for diseases. In Angola, primary healthcare is a recent and developing reality.